Conjugated Donor–Acceptor Terpolymers Toward High‐Efficiency Polymer Solar Cells. Issue 22 (30th January 2019) - Dang, Dongfeng; Yu, Donghong; Wang, Ergang
Abstract: The development of conjugated alternating donor–acceptor (D–A) copolymers with various electron‐rich and electron‐deficient units in polymer backbones has boosted the power conversion efficiency (PCE) over 17% for polymer solar cells (PSCs) over the past two decades. However, further enhancements in PCEs for PSCs are still imperative to compensate their imperfect stability for fulfilling practical applications. Meanwhile development of these alternating D–A copolymers is highly demanding in creative design and syntheses of novel D and/or A monomers. In this regard, when being possible to adopt an existing monomer unit as a third component from its libraries, either a D′ unit or an A′ moiety, to the parent D–A type polymer backbones to afford conjugated D–A terpolymers, it will give a facile and cost‐effective method to improve their light absorption and tune energy levels and also interchain packing synergistically. Moreover, the rationally controlled stoichiometry for these components in such terpolymers also provides access for further fine‐tuning these factors, thus resulting in high‐performance PSCs. Herein, based on their unique features, the recent progress of conjugated D–A terpolymers for efficient PSCs is reviewed and it is discussed how these factors influence their photovoltaic performance, for providing useful guidelines to design new terpolymers toward high‐efficiency PSCs. Abstract : In contrast to conjugated donaor–acceptor (D–A) alternating copolymers, incorporating a third component, either D′‐ or A′‐unit, to their D–A type polymer backbones can improve their light absorption, and tune energy levels and interchain packing synergistically. Moreover, the well‐controlled stoichiometry for these components in terpolymers also provides further access to fine‐tune these factors, thus resulting in high photovoltaic performance in polymer solar cells.